TINGKAT PENGETAHUAN TENTANG ANEMIA MENENTUKAN PERILAKU PENCEGAHAN ANEMIA PADA IBU HAMIL - Irin Kurniyawati; Yanita Trisetiyaningsih (MEDIA ILMU KESEHATAN, 2012)
Background: Health problems in Indonesia are still largely concerned with the health of the mother. Maternal mortality rate (MMR) in Indonesia has reached 307/100.000 births. The prevalence of pregnant women with iron deficiency is around 35-75%. One effort to overcome this is to monitor the health of the mother and fetus, especially during the period of pregnancy with a visit to the health service. In order to raise awareness for more regular antenatal visits, it requires sufficient knowledge in pregnant women about the dangers of anemia. Objective: This study aimed to determine the relationship of the level of pregnant women’s knowledge about anemia to the behavior of anemia prevention in Sleman Health Center of Yogyakarta. Methods: This was a quantitative descriptive correlation study using a cross sectional approach. The population was pregnant women who were in the work area of Sleman Health Center, Yogyakarta. The total samples were 78 and data collection used questionnaires. Data analysis used univariable and bivariable analysis. The results: The level of pregnant women’s knowledge on anemia was mostly on moderate categories (57.7%). Preventive behavior done by the pregnant women was mostly in the categories of risk behaviors of health disorders (48.7%). Statistically there was a significant relationship between the level of pregnant women’s knowledge on anemia and the behavior of anemia prevention with a value of p = 0.000. This shows that there was a correlation between pregnant women’s knowledge on anemia and anemia prevention behavior. Conclusion: Pregnant women’s knowledge on anemia determines maternal behavior in efforts to prevent anemia. To prevent anemia in pregnant women, health workers are expected to provide health education to all pregnant women for health examination. Keywords: Knowledge, anemia, anemia prevention